EXPERIMENTAL STUDY OF ELEMENTARY MATHEMATICAL IMAGINATIONS OF MENTALLY DISABLED STUDENTS - Muyassar Khamidova (The Bioscan, 2024)
This article reveals the state of development of elementary mathematical skills in students with mental retardation. The condition of mentally retarded students' perception of size, solving simple problems, quantitative perception, concept of geometric shape, spatial and time perception was determined and analyzed. As a result of the experimental research, the perception of size, solving simple problems, quantitative perception, concept of geometric shape, mastery of spatial and time concepts were studied by mentally retarded children.